1981
DOI: 10.1002/1098-2337(1981)7:2<97::aid-ab2480070203>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent and predictive validity of self-reported aggressiveness

Abstract: The subjects (60 boys) were drawn from the sample of a longitudinal study of social development and represented extremely aggressive, anxious, constructive, and submissive behaviour at the age of 8. They were presented with three question series concerning (1) their responses to aggressive attacks; (2) reactions in frustration situations presented in short stories; and (3) their aggressive initiatives. In each series the type of aggressive behaviour, attacker, victim, and other situational factors were systema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1982
1982
2001
2001

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…The technique used to measure aggression in the current study and the Eron et al 10-year study yielded an internal consistency of .97, a 1month stability of .91, and a 10-year stability of .38. In Finland, similar findings over a 10year period have been reported by Pitkanen-Pulkkinen (1981).…”
supporting
confidence: 85%
“…The technique used to measure aggression in the current study and the Eron et al 10-year study yielded an internal consistency of .97, a 1month stability of .91, and a 10-year stability of .38. In Finland, similar findings over a 10year period have been reported by Pitkanen-Pulkkinen (1981).…”
supporting
confidence: 85%
“…It was found that proactive aggression of any type and reactive physical aggression to attacks of the same-sized, same-sex peer, predicted adult aggression ten years later. This conclusion was based on the predictive validity of the Question Series (Pitkänen-Pulkkinen, 1981) and the PAM (Pitkänen-Pulkkinen, 1980). Insight 9 is that the delay of aggressive response indicates self-control.…”
Section: <Figure 1 Here>mentioning
confidence: 99%
“…Furthermore, a considerable body of criminological literature using self-and other's reports of aggressive behaviour finds that self-report is highly correlated with external validity criteria such as school infractions and police contacts (Farrington, 1973). In a longitudinal study, Pitkanen-Pulkkinen (1981) found self-predicted aggression in children aged eight to be significantly associated with concurrent and predictive validity indices.…”
Section: Anne Campbell Daniel Bibel and Steven Muncermentioning
confidence: 99%